Analisis Pengetahuan dengan Kejadian Anemia pada Ibu Hamil di Puskesmas X: Analysis of Knowledge on The Incident of Anemia in Pregnant Women at Public Health Center X - Fera Aldania; Masruroh (Universitas Ngudi waluyo, 2024)
Anemia is a condition where the number and size of red blood cells or hemoglobin concentration is below the normal limit value and in pregnant women this occurs due to hemodilution. The number of pregnant women at the Kledung Community Health Center in January – December 2021 was 198 people and 53 people (26.76%) of them had anemia, while the number of pregnant women in January – October 2022 was 265 people and 110 people (41.50%) of them suffer from anemia. Factors that influence anemia are lack of knowledge. The aim of the research was to determine the relationship between the level of knowledge of pregnant women about anemia and the incidence of anemia in pregnant women at the Kledung Community Health Center Temanggung. This research is a type of quantitative research in the form of analytical survey research with a cross sectional research design. Collecting primary data with questionnaires and secondary data from the cohort of pregnant women at the Kledung Community Health Center Temanggung. The sampling was carried out using a total population technique of 49 respondents. Data analysis used chi-square. The level of knowledge of pregnant women about anemia in the good category was 17 people (34.7%), 20 people (40.8%) were sufficient and 12 people (24.5%) were poor. The incidence of anemia in pregnant women was 24 people (49%). The results of statistical tests using Chi-Square showed p-value = 0.019 (p<0.05) so that there was a relationship between the level of knowledge of pregnant women about anemia and the incidence of anemia in pregnant women at the Kledung Community Health Center Temanggung. There is a relationship between anemia and the incidence of anemia in pregnant women at the Kledung Community Health Center Temanggung in 2022. Abstrak Anemia adalah suatu keadaan dimana jumlah dan ukuran sel darah merah atau konsentrasi hemoglobin dibawah nilai batas normal dan pada ibu hamil terjadi karena hemodilusi. Jumlah ibu hamil di Puskesmas Kledung pada bulan Januari – Desember 2021 sebanyak 198 orang dan 53 orang (26,76%) diantaranya mengalami anemia, sedangkan jumlah ibu hamil bulan Januari – Oktober 2022 sebanyak 265 orang dan 110 orang (41,50%) diantaranya mengalami anemia. Faktor yang mempengaruhi anemia yaitu kurangnya pengetahuan. Tujuan penelitian untuk mengetahui hubungan tingkat pengetahuan ibu hamil tentang anemia dengan kejadian anemia pada ibu hamil di Puskesmas Kledung Temanggung. Penelitian ini merupakan jenis penelitian kuantitatif dengan bentuk penelitian survei analitik dengan desain penelitian cross sectional. Mengumpulkan data primer dengan kuesioner dan data sekunder dari kohort ibu hamil Puskesmas Kledung Temanggung. Pengambilan sampel dilakukan dengan teknik total populasi sebanyak 49 responden. Analisis data menggunakan chi-square. Tingkat pengetahuan ibu hamil tentang anemia kategori baik sebanyak 17 orang (34,7%), cukup sebanyak 20 orang (40,8%), dan kurang sebanyak 12 orang (24,5%). Kejadian anemia pada ibu hamil sebanyak 24 orang (49%). Hasil uji statistik dengan Chi-Square didapatkan p-value = 0,019 (p<0,05) sehingga terdapat hubungan antara tingkat pengetahuan ibu hamil tentang anemia dengan kejadian anemia pada ibu hamil di Puskesmas Kledung Temanggung. Ada hubunagna antar tentang anemia dengan kejadian anemia pada ibu hamil di Puskesmas Kledung Temanggung 2022.